2019
DOI: 10.1101/837161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Removal of high frequency contamination from motion estimates in single-band fMRI saves data without biasing functional connectivity

Abstract: AbstractDenoising fMRI data requires assessment of frame-to-frame head motion and removal of the biases motion introduces. This is usually done through analysis of the parameters calculated during retrospective head motion correction (i.e., ‘motion’ parameters). However, it is increasingly recognized that respiration introduces factitious head motion via perturbations of the main (B0) field. This effect appears as higher-frequency fluctuations in the motion parameters (> 0.1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…As such, even though there appeared to be little effect of motion in isolation, careful consideration should be applied to interpretations made regarding results within these domains. Future work would benefit from combinations of ICA, nuisance spectra (Fair et al, 2020; Gratton et al, 2019) and data-driven optimization not only to isolate signal of interest, but also design objective filters to minimize artifact, as artifact and signal of interest may not be compartmentalized to the evenly-spaced frequency bins selected for this analysis. Were such approaches to be utilized, they would need to be robust to acquisition parameters such as the Nyquist frequency limits set by the TR, and signal-and-artifact frequency overlap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, even though there appeared to be little effect of motion in isolation, careful consideration should be applied to interpretations made regarding results within these domains. Future work would benefit from combinations of ICA, nuisance spectra (Fair et al, 2020; Gratton et al, 2019) and data-driven optimization not only to isolate signal of interest, but also design objective filters to minimize artifact, as artifact and signal of interest may not be compartmentalized to the evenly-spaced frequency bins selected for this analysis. Were such approaches to be utilized, they would need to be robust to acquisition parameters such as the Nyquist frequency limits set by the TR, and signal-and-artifact frequency overlap.…”
Section: Discussionmentioning
confidence: 99%
“…As with any fMRI study, the effects of motion may significantly contribute to the measured BOLD signals, particularly long vs. short range FNC values. Furthermore, recent work has identified that short TR multi-band sequences have respiration artifacts that have alias with motion estimates, and without information specific to respiration (e.g., waist bellows), notch filtering is recommended to mitigate respiration (Fair et al, 2020; Gratton et al, 2019). For the current study, however, motion measures likely mixed with respiration were fitted as a single regressor, both to avoid the loss of frequency-specific information associated with notch filtering, and because respiration information was not collected in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our findings on age-related change in amygdala and mPFC function may be biased or confounded by age-related differences in head motion 70 , anatomical image quality and alignment 71,72 , signal dropout, and physiological artifacts [73][74][75] An accelerated longitudinal design was used such that participants' starting ages at scan 1 comprised the entire range of sample ages (4-22 years old), and coverage was approximately balanced across the entire age range (see Figure 1B). The design was structured into 3 study 'waves' corresponding with recruitment efforts and visit protocols.…”
Section: Limitationsmentioning
confidence: 99%
“…For the single band data (TR=2500ms), this filter is also not applicable (Nyquist frequency = 0.2Hz). We then attempted the technique suggested by Gratton et al 111 and applied a low-pass filter with a cutoff frequency at 0.1Hz. Motion parameters (FD) were recalculated after applying each of the filters.…”
Section: Usage Notesmentioning
confidence: 99%